Retreatability of calcium silicate‐based root canal sealer using reciprocating instrumentation with different irrigation activation techniques in single‐rooted canals. (20th December 2021) - Angerame, Daniele; De Biasi, Matteo; Porrelli, Davide; Bevilacqua, Lorenzo; Zanin, Riccardo; Olivi, Matteo; Kaitsas, Vassilios; Olivi, Giovanni
Abstract: This study analysed the bioceramic sealer cleaning ability of two chemo‐mechanical systems in intact and restored teeth. Thirty‐two single‐rooted teeth were used, and half of them restored with a pre‐endodontic composite restoration (PCR). All samples were instrumented with a size 40 Reciproc Blue file and filled with BioRoot RCS. Canals were retreated using the R40 and then R50 Reciproc Blue. The samples were divided into four experimental groups ( n  = 8): intact teeth/passive ultrasonic irrigation (PUI) (G1), intact teeth/shock wave‐enhanced emission photoacoustic streaming (SWEEPS) (G2), PCR/PUI (G3) and PCR/SWEEPS (G4). The samples were scanned by micro‐CT before and after retreatment, and the volume of remaining filling material was evaluated. The minor percentage of residues were observed in G2, with a volume of 0.447 ± 0.356% of the endodontic space ( P  < 0.001). The Reciproc/SWEEPS technique showed the better performance in intact teeth compared with PUI technique. Pre‐endodontic restoration did not significantly affect the effectiveness of sealer removal.